PPAR-Alpha Agonist Fenofibrate Combined with Octreotide Acetate in the Treatment of Acute Hyperlipidemia Pancreatitis - Wen Bao; Rui Kong; Nan Wang; Wei Han; Jie Lu (PPAR Research)
At present, there are more and more patients with acute hypertriglyceridemia pancreatitis in clinical practice. Common treatment measures include fasting and water withdrawal, fluid resuscitation, and somatostatin. In recent years, studies have pointed out that the PPARa agonist fenofibrate may help improve the condition of such patients. Therefore, through clinical research and analysis, we reported for the first time that fenofibrate combined with octreotide acetate has a more excellent effect in the treatment of patients with acute hypertriglyceridemia pancreatitis, and from the perspective of signal pathways, we revealed that the combination of the two drugs has an effect on NF-κB P65. The synergistic inhibitory effect proves that the combined treatment is beneficial to control inflammation, protect liver function, and improve the prognosis of patients. It is worthy of clinical promotion.